Prenatal arsenic exposure stymies gut butyrate production and enhances gut permeability in post natal life even in absence of arsenic deftly through miR122-Occludin pathway. (1st February 2023) - Chakraborty, Mainak; Gautam, Anupam; Das, Oishika; Masid, Aaheli; Bhaumik, Moumita
Abstract: This discourse attempts to capture a few important dimensions of gut physiology like microbial homeostasis, short chain fatty acid (SCFA) production, occludin expression, and gut permeability in post-natal life of mice those received arsenic only during pre-natal life. Adult Balb/c mice were fed with 4 ppm arsenic trioxide in drinking water during breeding and gestation. After the birth of the pups, the arsenic water was withdrawn and replaced with clean drinking water. The pups were allowed to grow for 28 days (pAs-mice) and age matched Balb/c mice which were never exposed to arsenic served as control The pAs-mice showed a striking reduction in Firmicutes to Bacteroidetes (F/B) ratio coupled with a decrease in tight junction protein, occludin resulting in an increase in gut permeability, increased infiltration of inflammatory cells in the colon and decrease in common SCFAs in which butyrate reduction was quite prominent in fecal samples as compared to normal control. The above phenotypes of pAs-mice were mostly reversed by supplementing 5% sodium butyrate (w/w) with food from 21st to 28th day. The ability of butyrate in enhancing occludin expression, in particular, was dissected further. As miR122 causes degradation of Occludin mRNA, we transiently overexpressed miR122 by injecting appropriate plasmids and showed reversal of butyrate effects in pAs-mice. Thus, pre-natal arsenic exposure orchestrates variety of effects by decreasing butyrate in pAs-mice leading to increased permeability due to reduced occludin expression. Our research adds a new dimension to our understanding that pre-natal arsenic exposure imprints in post-natal life while there was no further arsenic exposure. Highlights: Prenatal Arsenic exposure decreases prevalence of butyrate producing bacteria and butyrate production in the gut. Lack of butyrate production in the gut is responsible for increased permeability and decreased occludin expression. Oral supplementation with butyrate reverses the prenatal arsenic induced changes in the gut. Butyrate increases Occludin gene expression by downregulating miR122 in the gut.